The use of alternative liquid media for propagation of pathogenic fungi and their effect on weeds - Loekas Soesanto; Endang Mugiastuti; Abdul Manan (Society for Indonesian Biodiversity, 2021)
Abstract. Soesanto L, Mugiastuti E, Manan A. 2021. The use of alternative liquid media for propagation of pathogenic fungi and their effect on weeds. Biodiversitas 22: 719-725. Weeds cause high yield losses and are controlled by chemical, physical and mechanical control. Weed pathogenic fungi could be used as a biological control agent. However, the propagation media of them are still a higher cost, therefore, the new alternative and inexpensive media for weed pathogenic fungi propagation are required. The propagation of weed pathogenic fungi in liquid media in-vitro used randomize completely design consisted of three pathogenic weed fungi, i.e., Chaetomium sp., Fusarium sp., and Curvularia lunata and three liquid media, i.e., PDB, rice washing water, and tofu liquid waste. The in-planta tests used split-plot design used weed pathogenic fungi multiplied in the best formula from in-vitro results (rice washing water) and control as the main plot and four weeds, i.e., Cyperus kyllingia, Cynodon dactylon, Portulaca oleracea, and Ageratum conyzoides as subplot. The variables observed were conidia density, incubation period, disease intensity, number of leaves, and weed height. The results showed that rice washing water and tofu liquid waste were suitable media for the propagation of the weed pathogenic fungi. Chaetomium sp. was virulent fungi against broad leaves weeds, especially A. conyzoides. This fungus can be promoted to manufacture organic herbicides against the weed.